1981
DOI: 10.2527/jas1981.52151x
|View full text |Cite
|
Sign up to set email alerts
|

Mature Weight, Maturation Rate, Maternal Performance and Their Interrelationships in Purebred and Crossbred Cows of Angus and Milking Shorthorn Parentage

Abstract: Mature weight, maturation rate and lifetime maternal performance, through a maximum of seven calving seasons, were analyzed for 182 cows of Angus (A) and Milking Shorthorn (S) breeds and the two reciprocal crossbred groups. Mature weight and rate of maturation were estimated for the three-parameter growth curve described by Brody. Estimates derived for mature weight (kilograms), both unadjusted and adjusted for cow condition, were, respectively: Angus, 421, 407; Shorthorn, 409, 459; A x S, 448, 455 and S x A, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 8 publications
1
15
0
Order By: Relevance
“…Although not significant, weaned weight per cow exposed per year decreased by 17 kg for each 100-kg increment of A, in close agreement with the data of Stewart and Martin (1981).…”
Section: Effects Of Growth Curve Parameterssupporting
confidence: 88%
“…Although not significant, weaned weight per cow exposed per year decreased by 17 kg for each 100-kg increment of A, in close agreement with the data of Stewart and Martin (1981).…”
Section: Effects Of Growth Curve Parameterssupporting
confidence: 88%
“…T anida et al (1988) reported negative genetic correlations between longevity (survival from first calving to disposal) and weaning weight in the Hereford breed. S tewart and M artin (1981) also observed that the number of calves produced by a cow in her lifetime decreased with increasing mature weight in Angus and Milking Shorthorns. Consideration of cow size in voluntary culling decisions by producers is minor relative to reproductive soundness and conformation.…”
Section: Resultsmentioning
confidence: 81%
“…In high production environments, larger cows with greater milk production are able to maximize genetic potential for growth (Holloway and Butts, 1984;Nunez-Dominguez et al, 1993). This correlation of WW with mature cow size has been suggested to result in an increase of 0.04 to 0.13 kg in WW for every 1-kg increase in mature cow weight under optimal conditions (Urick et al, 1971;Stewart and Martin, 1981;Doye and Lalman, 2011). However, in limited production environments such as the McGuire Ranch in Wyoming, cows with greater maintenance requirements due to body size and milk potential may not reach their genetic potential for growth and may not be as efficient in calf weight relative to dam size (Buttram and Willham, 1989).…”
Section: Discussionmentioning
confidence: 99%